Enhancing preparation and planning in cross-cultural negotiation - Kam, Yee Khoon (2008)
This paper presents a two-level model on the negotiation process: the first level (Culture-incorporated Negotiation Learning Model) deals with generic culture considerations applied at the different levels, and the second level (DeAL Negotiation Preparation and Planning Model) details specific thought processes during preparation and planning.